Dating SOS: a systematic and theory-based development of a web-based tailored intervention to prevent dating violence among Brazilian youth - Sheila Giardini Murta; Priscila de Oliveira Parada; Sara da Silva Meneses; João Victor Venâncio Medeiros; Amanda Balbino; Marina Caricatti Rodrigues; Marco Akira Miura; Thiago André Araújo dos Santos; Hein de Vries (BMC, 2020)
Abstract Background Dating violence has an alarming prevalence among Brazilian adolescents. School-based preventive programs have been implemented, but remain isolated initiatives with low reach. Health communication strategies based on innovative technologies with a high potential of diffusion are urgent. This study aimed to develop a computer-tailored intervention to prevent victimization and perpetration of dating violence among Brazilian youth. Methods The intervention, called Dating SOS (SOS Namoro), is based on the I-Change Model and attachment theory and is a comprehensive preventive program targeted to young people with a current partner. The intervention design included the stages of needs assessment; definition of objectives of change; development of the library of messages; elaboration of a questionnaire for tailoring feedbacks according to the relevant variables; integration of the content in the software Tailor Builder; pre-testing; and usability and efficacy evaluation planning. Dating SOS is composed of four online sessions. The first session gives a tailored orientation on attachment style and risk perception of violence. The second session addresses knowledge on conflict management, positive and negative social models of intimate relationships and an action plan to improve everyday interactions. The third session covers social norms, self-efficacy and an action plan to cope with conflicts. The fourth session discusses attitudes, social support and an action plan to protect from violence. Improvements on the interface and tailoring refinement was done after pre-testing to improve attractiveness and decrease risk of iatrogenic effects. Discussion The principal merit of the present study resides in the development of an innovative strategy based on the qualified use of the internet for education surrounding romantic relationships and the prevention of dating violence among adolescent and young Brazilians, a hitherto unaddressed need in the field. The intervention usability and efficacy should be investigated in further studies. Trial registration Brazilian Registry of Clinical Trials. RBR-9frj8q. Prospectively registered on July 25, 2019. http://www.ensaiosclinicos.gov.br/rg/RBR-9frj8q/